Absorption of Heavy Metal Lead Using Floating Aquatic Plants (Duckweed, Lemna Minor) - Yashikharan, Ishan; Hamidon, Nuramidah (Progress in Engineering Application and Technology, 2023)
Heavy metal contamination of surface water is a serious problem that effects the livelihood of the people, flora and fauna around the globe. The main objective of this research is to determine the chemical properties of Sungai Panchor and investigate the effectiveness of duckweed (Lemna Minor) in absorbing heavy metal lead (Pb) from the surface water of Sungai Panchor by using the process of phytoremediation. Turbidity, pH, dissolved oxygen (DO) and heavy metal lead were the parameters for this experiment. Duckweed was left in the water sample for nine days and the results of the four parameters were taken before and after the experiment. After nine days, the water quality improved, which can be proven by the increase of dissolved oxygen, from 0.96 mg/L to 8.65 mg/L, and the decrease of concentration of lead, from 69.67 μg/L to 44.67 μg/L. Turbidity and pH also decreased from 7.54 NTU to 1.85 NTU and from 8.30 to 5.31 respectively. The duckweed shows a removal percentage of lead of 35.88%. To improve the effectiveness of duckweed in absorbing lead from Sungai Panchor, a fence or border can be built so that the plants are not disturbed by waves from boats and the flow of the river.